"It's gym, like g-y-m not J-i-m": Exploring the role of place in the gendering of physical activity. (January 2018) - Coen, Stephanie E.; Rosenberg, Mark W.; Davidson, Joyce
Abstract: Physical activity is a highly gendered health behaviour, with women less likely than men to meet internationally accepted physical activity guidelines. In this article, we take up recent arguments on the potential of indoor spaces to illuminate processes shaping health, together with social theories of gender, to conceptualize the place of the gym as a window into understanding and intervening in wider gender disparities in physical activity. Using a triangulated strategy of qualitative methods, including semi-structured interviews, drawing, and journaling with men and women in a mid-sized Canadian city, we examine how gender influences exercise practices and mobilities in gym environments. Results of our thematic analysis reveal three socio-spatial processes implicated in the gendering of physical activity: 1) embodying gender ideals, 2) policing gender performance, and 3) spatializing gender relations. A fourth theme illustrates the situated agency some individuals enact to disrupt gendered divisions. Although women were unduly disadvantaged, both women and men experienced significant limitations on their gym participation due to the presiding gendered social context of the gym. Gender-transformative interventions that go beyond engaging women to comprehensively contend with the place-based gender relations that sustain gender hegemony are needed. While gyms are potentially sites for health promotion, they are also places where gendered inequities in health opportunities emerge. Highlights: Geographies of physical activity rarely focus on gendered inequities. We examine the gym as a window into gender disparities in physical activity. Qualitative analysis reveals three socio-spatial gendering processes. Women and men experienced limitations on participation due to gendering processes. Gender-transformative interventions must target everyday physical activity places.